2003
DOI: 10.1046/j.1444-2906.2003.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity change on free amino acid content in Pacific oyster

Abstract: In order to identify free amino acids (FAA) that are importantas intracellular osmolytes in Crassostrea gigas, we investigatedthe change in FAA content in the mantle exposed to an abrupt decreaseor increase in salinity. In hypo‐osmotic adaptation, most FAA showedremarkable and synchronous decreases from 2 to 8 h, suggestingthat the non‐selective efflux of FAA was mainly responsible forthe decrease in FAA. Taurine that accounted for approximately 80% oftotal FAA content contributed most significantly to the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 12 publications
13
94
0
2
Order By: Relevance
“…Adult bivalves have been observed to present rather slow rates of taurine synthesis, at least insufficient to explain the high amounts encountered in their tissues (Bishop et al 1983) which in turn has suggested that individuals must acquire taurine per se from dietary sources (Hosoi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Adult bivalves have been observed to present rather slow rates of taurine synthesis, at least insufficient to explain the high amounts encountered in their tissues (Bishop et al 1983) which in turn has suggested that individuals must acquire taurine per se from dietary sources (Hosoi et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of lipid biosynthesis appears to be a less likely explanation of the reduced lipid content in oysters maintained under low salinity conditions. Acclimation to low salinity led to a shift in the metabolic profile in oysters, notably to a strong reduction in the levels of betaine and alanine (by approximately 70 and 40%, respectively), consistent with their role as major osmolytes in bivalves (Powell et al, 1982;Neufeld and Wright, 1996;Hosoi et al, 2003). In contrast, elevated P CO2 had no effect on the metabolite profile in whole bodies of oyster juveniles in this study except for the lower acetate content of tissues from hypercapnic juveniles compared with their normocapnic counterparts at a salinity of 15.…”
Section: Effects Of P Co2 and Salinity On Energy Homeostasis Of Juvenmentioning
confidence: 99%
“…Many papers have reported on the biological and ecological aspects, and have gradually determined the chemical components in the oyster tissues, such as glycogen 3 and amino acids 4 . However, there is as yet little comparative study of C. gigas under the different environmental conditions between the two countries.…”
Section: Introductionmentioning
confidence: 99%